Identification of Lactic Acid Bacteria Inhibiting the Growth of Saccharomyces cerevisiae in Molasses Fermentation - Vico, Yoel; Budiarso, Tri Yahya; Amarantini, Charis; Setyaningsih, Ratna (Biosaintifika: Journal of Biology & Biology Education, 2025)
Ethanol production by Saccharomyces cerevisiae is essential for the biofuel industry, but microbial contamination by Lactic Acid Bacteria (LAB) can significantly reduce yield and fermentation efficiency. This research aimed to identify Lactic Acid Bacteria (LAB) causing significant inhibition of Saccharomyces cerevisiae growth. LAB isolates were screened and identification was carried out by carbohydrate fermentation using the 50 CHL Analytical Profile Index (API) Kit, and the LAB isolates (MC2K1, MP2K1, and MP2K2) were identified as Lactobacillus rhamnosus and isolate MC2K2 as L. pentosus. The results demonstrated that bacteriocins did not significantly inhibit S. cerevisiae following heat treatment, indicating that metabolic byproducts, particularly lactic acid, were primarily responsible for yeast inhibition. Co-culture of LAB and S. cerevisiae supernatants was used to determine inhibition by metabolites produced by LAB. A higher inhibitory effect occurred in the supernatant from 48 hours of incubation with lower CFU results. The highest inhibition rate reached 42% in isolate MC2K1 and the incubation time of 6 hours with all isolates significantly inhibited the growth of S. cerevisiae. These findings challenge the prevailing assumption that bacteriocins are the primary inhibitors of yeast and highlight the importance of metabolic byproducts as dominant inhibitory factors. This insight contributes to developing targeted contamination control strategies, ultimately enhancing ethanol production efficiency.